2018
DOI: 10.1128/mbio.02327-17
|View full text |Cite
|
Sign up to set email alerts
|

Adjustments to Photosystem Stoichiometry and Electron Transfer Proteins Are Key to the Remarkably Fast Growth of the Cyanobacterium Synechococcus elongatus UTEX 2973

Abstract: At the genome level, Synechococcus elongatus UTEX 2973 (Synechococcus 2973) is nearly identical to the model cyanobacterium Synechococcus elongatus PCC 7942 (Synechococcus 7942) with only 55 single nucleotide differences separating the two strains. Despite the high similarity between the two strains, Synechococcus 2973 grows three times faster, accumulates significantly more glycogen, is tolerant to extremely high light intensities, and displays higher photosynthetic rates. The high homology between the two st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
92
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(104 citation statements)
references
References 23 publications
8
92
1
Order By: Relevance
“…Cyanobacterial NDH-1 complexes participate in cyclic electron flow around PSI, respiratory electron flow, and CO 2 uptake [29][30][31] . An increase in PSI activity at high light can dissipate pressure in the electron transport chain; a similar phenomenon was reported to contribute to high-light tolerance and faster growth in Synechococcus elongatus UTEX 2973 compared to its close relative Synechococcus PCC 7942 32 . Interestingly, the high-light responsive transcription factor RpaB (slr0947, regulator of phycobilisome association B) was also up-regulated in multiple mutants.…”
Section: Mutants With a Growth Advantagesupporting
confidence: 53%
“…Cyanobacterial NDH-1 complexes participate in cyclic electron flow around PSI, respiratory electron flow, and CO 2 uptake [29][30][31] . An increase in PSI activity at high light can dissipate pressure in the electron transport chain; a similar phenomenon was reported to contribute to high-light tolerance and faster growth in Synechococcus elongatus UTEX 2973 compared to its close relative Synechococcus PCC 7942 32 . Interestingly, the high-light responsive transcription factor RpaB (slr0947, regulator of phycobilisome association B) was also up-regulated in multiple mutants.…”
Section: Mutants With a Growth Advantagesupporting
confidence: 53%
“…The cyanobacterium with the highest known photoautotrophic growth rate, growing with a doubling time of up to T D ∼ 1.9h, is the strain Synechococcus elongatus UTEX 2973. Compared to its closest relative, Synechococcus elongatus PCC 7942, the strain shows several physiological adaptation, such as higher PSI and cytochrome b 6 f content per cell (Ungerer et al, 2018), lower metabolite pool in central metabolism, less glycogen accumulation, and higher electron charge (Abernathy et al, 2017). Recently, high light was reported to promote the transcription of genes associated with central metabolic pathways, repression of phycobilisome genes, and accelerated glycogen accumulation rates (Tan et al, 2018) While these studies point to strain-specific differences and are important for characterizing non-model microbial metabolism (Abernathy et al, 2017), the general principles of resource allocation in photoautotrophic metabolism and the laws of phototrophic growth are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, only few studies so far have addressed the limits of cyanobacterial growth from an experimental perspective (Bernstein et al, 2016;Yu et al, 2015;Abernathy et al, 2017;Ungerer et al, 2018). Of particular interest were the adaptations that enable fast photoautotrophic growth (Bernstein et al, 2016;Yu et al, 2015;Abernathy et al, 2017;Ungerer et al, 2018). The cyanobacterium with the highest known photoautotrophic growth rate, growing with a doubling time of up to T D ∼ 1.9h, is the strain Synechococcus elongatus UTEX 2973.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an exciting development is the characterization of Synechococcus elongatus UTEX 2973 (Yu et al ), which appears to have a superior growth rate as compared to many other cyanobacteria. In a recent publication the authors reported its maximal growth rate to be 0.46 h −1 , quoted as a doubling time of 1.5 h (Ungerer et al ). Unfortunately, these latter numbers are a bit ambiguous because the experiment from which they were derived, is described to be performed at 42°C in the text of the paper and at 38°C in the legend of the relevant figure (Fig.…”
Section: Introductionmentioning
confidence: 99%